The effect of a collective competence intervention on collective efficacy, psychological wellbeing, and social wellbeing: a quasi-experimental study of a sample of healthcare workers during the COVID-19 crisis - Campos, María Lourdes; Bolgeri, Pedro; Bascur, Axel (Frontiers in Psychology, 2024)
Background: The health crisis associated with COVID-19 led to a period of increased demand on the operational and social organization of healthcare centers, which often had a negative impact on the psychological and social well-being of healthcare workers. In order to tackle this issue, an intervention plan was designed to develop collective competences through various participatory strategies. This study sought to determine the effect of this intervention on the variables Collective Efficacy, Psychological Well-Being, and Social Well-Being in healthcare workers by performing a pretest and posttest comparison with a control group. Method: The variables were evaluated using a non-probability, purposive sample of 80 healthcare workers from three Family Healthcare Centers (CESFAM) located in the Coquimbo Region, Chile, within health crisis context. The intervention group was composed of voluntary participants, while the control group only completed the evaluations. The intervention consisted in 6 training workshops focused on improving collective management, group synergy, collaborative problem-solving, communicative strategies, and overall team care. Results: The analysis shows that the collective competence intervention had a positive effect on the collective efficacy, psychological well-being, and social well-being of the participating healthcare workers during the COVID-19 crisis. Only specific factors of these variables did not undergo a significant impact. Conclusion: The results of this study suggest that interventions aimed at improving collective organizational competences, apart from increasing collective efficacy, can have a positive impact on healthcare workers' psychological and social well-being in a context of occupational adversity.